Applied big data analytics in operations management - Manish Kumar (Advances in business information systems and analytics, 2017)
Operations management is a tool by which companies can effectively meet customers' needs using the least amount of resources necessary. This volume enumerates the challenges and creative solutions and tools to apply when using big data in operations management.